(untitled) - Jagelcak, Juraj (Doprava a spoje, 2012)
Shipper has to take into account correct load distribution when railway wagons are loaded. Incorrectly loaded wagon is refused for further carriage. UIC loading guidelines define the requirements how railway wagon shall be loaded. These requirements are valid also for intermodal wagons. The paper focuses on intermodal wagon Sgnss 60' as wagon suitable for different types of intermodal loading units (ILU's). Besides that stowage of containers depends on the displacement of container fixing points load distribution depends not only on the position of ILU's but also on the stowage of cargo inside ILU's. The risk of overloading increases with the ILU weight and the eccentricity of the centre of gravity of ILU. The aim of the paper is to show the possibility to construct wagon load distribution diagram and analyse load distribution for different ILU's. Maximum eccentricity of ILU centre of gravity was 5 % according to the standard ISO 3874. Mainly unsymmetrical loading of 20' and 40' container and symmetrical loading of two 30' containers and two tank containers up to 35 tonnes was analysed.